The Balkans and Their Visual Dimensions in Albrecht Wirth’s Book ‘Der Balkan. Seine Länder und Völker...’ (1914) - Nikolay Chernokozhev (Zeszyty Cyrylo-Metodiańskie)
The proposed reflections focus on two main issues: 1) the selection of visual materials in Dr. Albrecht Wirth’s book 'Der Balkan. Seine Länder und Völker in Geschichte, Kultur, Politik, Volkswirtschaft und Weltverkehr' (Stuttgart, 1914), and 2) the interaction between the visual and verbal representations of the Balkans in this work. The volume includes 79 illustrations, consisting of reproductions of paintings and photographs, as well as one map. The author concludes that the visual materials in the book reinforce the widely accepted notion of Balkan diversity. At the same time, within the book’s covers, Dr. Wirth’s personal perspectives and academic voice are interwoven with a range of visual styles that support and sometimes challenge his narrative. This approach creates a layered portrayal that preserves the complexity and internal dynamics of the Balkan image for a German-speaking audience in the early 20th century. Original title in Bulgarian: Балканите и техните визуални измерения в книгата на Албрехт Вирт „Der Balkan. Seine Länder und Völker...“ (1914)